PURCHASE INTENTION PADA PRODUK BANK SYARIAH DITINJAU DARI BRAND AWARENESS DAN BRAND IMAGE DENGAN TRUST SEBAGAI VARIABEL MEDIASI - Raden Bagus Faizal Irany Sidharta; Ni Luh Ariningsih Sari; Wayan Suwandha (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Research aim to analyze influence of 1) Brand Awareness on Trust, 2) Brand Image on Trust, 3) Brand Awareness on Purchase Intention, 4) Brand Image on Purchase Intention, 5) Trust on Purchase Intention, 6) Brand awareness on Purchase Intention through Trust, 7) Brand image on Purchase Intention through Trust on sharia bank product. Sample has taken by using purposive sampling technique with 328 respondents. Data analysis technique used is Path Analysis. The research showed that brand awareness has positive and not significant effect on trust, brand image has positive and significant effect on trust, brand awareness has positive and significant effect on purchase intention, brand image has positive and significant effect on purchase intention, trust has positive and significant effect on purchase intention, brand awareness has not significant effect on purchase intention through trust, brand image has significant effect on purchase intention through trust. The implication of this research would benefit to the management of sharia banking to formulating strategy for increasing market share of sharia banking in Indonesia.